Artificial Intelligence dan Pendidikan Agama Islam: Upaya Membangun Generasi Berakhlak di Era Digital - Ramadhansyah Ade Perdana Tumangger; Selamat Pohan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The development of Artificial Intelligence (AI) has brought significant changes to various aspects of life, including the field of education. The presence of AI offers opportunities to improve the quality of learning through personalized educational materials, broad access to information, and increased efficiency in teaching and learning processes. However, technological advancement also presents challenges, such as reduced social interaction, the spread of unverified information, and the degradation of moral and spiritual values. Therefore, Islamic Religious Education (IRE) plays a strategic role in shaping a generation that is not only intellectually competent but also possesses noble character. This article aims to examine the role of AI in Islamic education and strategies for building a morally upright generation in the digital era. The study employs a library research method with a descriptive-analytical approach. The findings indicate that AI can serve as an effective tool in Islamic Religious Education when used wisely and grounded in the values of the Qur’an and Sunnah. The integration of technology and Islamic character education is essential for developing a generation of Muslims who are excellent, adaptive, and possess noble moral character (akhlaqul karimah).